Quality of Life of Parents of Children with Autism Spectrum Disorder in Biratnagar - Rai, Munawatee; Bhandari, Menuka; Khadgi, Karishma (Journal of Biratnagar Nursing Campus, 2025)
Background: The developmental disorders in children, including Autism Spectrum Disorder (ASD), are disorders of early brain development. ASD causes impairments in communication and social interaction, which seriously hinder the daily functioning of children and severely impede their educational and social attainments. Parenting a child with ASD requires long-term care. This challenge affects parents’ psychological well‑being, including financial constraints, lack of social support, deficiencies of health services, and labeling with autism, ultimately affecting quality of life. The objective of the study was to find out the quality of life of parents of children with ASD. Method: A cross-sectional research design was used; 50 parents were sampled. Data were collected through an interview technique by using the WHOQOL-BREF scale and analyzed in descriptive and inferential statistics using SPSS version 16.0. Result: Most (92%) of the respondents reported that their quality of life is satisfactory i.e., neither good nor bad and only 6% had good quality of life. Among the four domains of quality of life, physical and psychological domains are associated with the occupation of the parents (p=0.022 and p=0.010 respectively). Overall quality of life is also associated with the occupation of the parents (p=0.021) Conclusion: The majority of the parents of children with autism spectrum disorder reported their quality of life quite satisfactory i.e., neither good nor bad. Among the four domains of quality of life i.e., Physical, Psychological, Social, and Environmental, physical and psychological domains are associated with the occupation of the parents. Parents need psychological support from the family, friends and other related professional. They also need social acceptance and support and must get to enjoy friendly environment.